Microwave characteristics of (Pb,Ca)(Fe,Nb,Sn)O-3 dielectric materials - Kucheiko, S; Choi, JW; Kim, HJ; Yoon, SJ; Jung, HJ (AMER CERAMIC SOC, 1997)
The dielectric properties of (Pb1-xCax){(Fe1/2Nb1/2)(1-y)-Sn-y}O-3 solid solutions, where 0.4 less than or equal to x less than or equal to 0.6, y = 0.05, 0.1, have been investigated at microwave frequencies, The replacement of Fe3+/Nb5+ by Sn4+ at the B-site of the perovskite structure considerably improves the loss quality factor Q and does not remarkably affect the dielectric constant epsilon(r) and the temperature coefficient of resonant frequency tau(f). The tau(f) value of nearly 0 ppm/degrees C can be realized for x = 0.55, New high-quality dielectric ceramics having epsilon(r) of 85.3-89.9, Q.f values of 7510-8600 GHz, and tau(f) of 0-9 ppm/degrees C were obtained at 1150 degrees C for 3 h sintering in air, The influence of the sintering atmosphere on dielectric properties was also investigated.
Keywords: CERAMICS; FREQUENCIES